Development of Problem-Based Student Worksheets to Improve Students’ Numeracy Skills in Managing Household Electricity Usage - Nurjannah, Tri; Ishafit, Ishafit (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Recent changes in Indonesia’s education policy, particularly the removal of the National Examination and its replacement with the National Assessment, aim to improve the quality of learning. One of the key components of the National Assessment is the Minimum Competency Assessment (AKM), which evaluates students’ literacy and numeracy skills. However, results from the Programme for International Student Assessment (PISA) indicate that Indonesian students’ numeracy skills are still relatively low, including those at SMA Negeri 1 Bantarsari, where no significant improvement has been observed over the past two years. This study aims to develop a problem-based Student Worksheet (LKPD) designed to enhance students’ numeracy skills in managing household electricity consumption. The research employed a Research and Development approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The participants were 12th-grade students at SMA Negeri 1 Bantarsari. The LKPD was validated by content and media experts, and its feasibility was assessed by both teachers and students. The results show that the LKPD received a validity score of 80 percent, indicating that it is highly suitable for use without the need for major revisions. Additionally, positive feedback from teachers and students suggests that the LKPD is effective for problem-based learning and can support the development of students’ numeracy skills. Therefore, the problem-based Student Worksheets is expected to serve as an innovative learning resource that enhances the quality of physics instruction and strengthens students’ numeracy literacy